PROBLEMATIKA PEMBELAJARAN MAHARAH AL-QIRA’AH DAN SOLUSI PEMECAHANNYA - Syah, Burhan Lukman; Aziz, Agus Umar Abdul (Tarbiyatuna Kajian Pendidikan Islam, 2024)
The purpose of learning Arabic in general is so that students can master Arabic properly and correctly. Learning maharah qiro'ah in Arabic at MA Madinatunnajah Sukabumi is part of the existing learning in Arabic which aims to make students able to read texts correctly according to the rules of Nahwu Sharaf, makhraj and their tajwid, able to translate and answer questions according to the text. This research uses qualitative research methods, data collection methods use interviews, observation, questionnaires, tests and documentation, to analyze the data that has been collected the author uses descriptive analysis methods. The results of this study are the implementation of Al-Qiro'ah learning activities at MA Madinatunnajah Sukabumi including objectives, curriculum, teachers, students, and methods. There are problems in learning including linguistic and non-linguistic problems, the solution to existing problems is that the teacher must have the ability to master the qiro'ah learning method and make preparations before teaching begins so that students are motivated in learning al-qiro'ah so that learning is effective and running well.